Implementasi Program Pemberdayaan Masyarakat Pesisir dalam Upaya Konservasi Sumber Daya Alam - Lestari, Sri; Komariyah, Fitri; Wahib, Moh.; Sadiqin, Amin (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
This research discusses the implementation of a coastal community empowerment program aimed at raising awareness of the importance of conserving natural resources in coastal areas. The program utilizes a participatory approach that integrates local knowledge with modern conservation practices to achieve sustainable goals. The research method used is a qualitative approach that involves active participation of coastal communities in all stages of the program. Data is collected through participatory observation, interviews, and group discussions, and analyzed thematically. The research findings indicate that involving coastal communities directly in conservation efforts has positive impacts both socially and environmentally. This empowerment program successfully enhances the awareness of coastal communities regarding the importance of conserving natural resources and strengthens their involvement in such efforts. In conclusion, coastal community empowerment is an effective approach to natural resource conservation, with the potential to create sustainable positive changes in coastal communities.